Epigenetic based synthetic lethal strategies in human cancers - Aiai Gao; Mingzhou Guo (BMC, 2020)
Abstract Over the past decades, it is recognized that loss of DNA damage repair (DDR) pathways is an early and frequent event in tumorigenesis, occurring in 40-50% of many cancer types. The basis of synthetic lethality in cancer therapy is DDR deficient cancers dependent on backup DNA repair pathways. In cancer, the concept of synthetic lethality has been extended to pairs of genes, in which inactivation of one by deletion or mutation and pharmacological inhibition of the other leads to death of cancer cells whereas normal cells are spared the effect of the drug. The paradigm study is to induce cell death by inhibiting PARP in BRCA1/2 defective cells. Since the successful application of PARP inhibitor, a growing number of developed DDR inhibitors are ongoing in preclinical and clinical testing, including ATM, ATR, CHK1/2 and WEE1 inhibitors. Combination of PARP inhibitors and other DDR inhibitors, or combination of multiple components of the same pathway may have great potential synthetic lethality efficiency. As epigenetics joins Knudson's two hit theory, silencing of DDR genes by aberrant epigenetic changes provide new opportunities for synthetic lethal therapy in cancer. Understanding the causative epigenetic changes of loss-of-function has led to the development of novel therapeutic agents in cancer. DDR and related genes were found frequently methylated in human cancers, including BRCA1/2, MGMT, WRN, MLH1, CHFR, P16 and APC. Both genetic and epigenetic alterations may serve as synthetic lethal therapeutic markers.